Multiple sclerosis and awereness In Turkey - Demir, S.; Tutuncu, M.; Togrol, R. E.; Kocaman, A. Sagduyu; Siva, A. (SAGE PUBLICATIONS LTD, 2019)
35th Congress of the European-Committee-for-Treatment-and-Research-in-Multiple-Sclerosis (ECTRIMS) / 24th Annual Conference of Rehabilitation in MS, Stockholm, SWEDEN, SEP 11-13, 2019